Nilai Estetika Sajak “Sisa-SisaUsia” Karya Soedjarwo dan “Sajak Orang Tua” Karya Rahmat Djoko Pradopo - Muzakka, Moh (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
The aesthetic study of poetry or poetry written by two authors is very rare, especially the two verses were compared to search for aesthetic concepts and trace their intertextual relationships. This short article attempts to describe and compare the aesthetic value of poem “ Sisa-Sisa Usia” by Soedjarwo  and "Sajak Orang Tua" by Rahmat Djoko Pradopo by using aesthetic approach as the main focus and approach of literature and intertextual as supporting. The results of the analysis show that the two poems have the same aesthetic value, both from the structure of sound, diction, meaning, the means of rhetoric or from its content, that is anxiety and submission of lyrics. From the similarity of structure and content it shows the existence of intercourse relationship